New learning of geography with technology: the TPACK model - Isabel María GÓMEZ TRIGUEROS (European Journal of Geography)
The increasing importance of technologies in the different aspects of life has led to the development of teaching and learning models such as the Technological Pedagogical Content Knowledge model that allows integrating technology, pedagogy and disciplinary knowledge. The main objective of this work is to evaluate the formative possibilities of this model for 240 students of the subject of "Didactics of Social Sciences: Geography of Primary Degree of the Faculty of Education of the University of Alicante, to elaborate didactic proposals of Geography with technology. The methodology implemented has been active and cooperative.The study is a mixed one, combining quantitative and qualitative analyzes based on two instruments: the questionnaire and the materials produced by the participants. The results show the acquisition of geographical knowledge, of digital competence and of active methodologies.